Does Ethical Leadership Lead to Happy Workers? A Study on the Impact of Ethical Leadership, Subjective Well-Being, and Life Happiness in the Chinese Culture - Yang, Conna (Journal of business ethics, 2014)
Business ethics has been emphasized throughout the past decade and organizations are aware of the influence it has on the organization’s performance. As a result, ethical leadership is important as it influences the employees profoundly. This study aims to address this issue and explore the influence ethical leadership has on employees by examining job satisfaction, subjective well-being at work, and life satisfaction. Two groups of independent data were collected and a multi-group analysis was conducted before pooling together for a two-step structural equation modeling test. The results revealed that ethical leadership has a negative direct effect on employee well-being which offers significant findings for the meaning of ethical leadership in the Chinese culture. Useful managerial implications are provided for managers and supervisors at the end of this study.